(3QSGdI Gdbhd aj GdfaS (B( (3GdeNJUQ ef CQSWh (B)s - (3CHh jYbhH Hf eMeO Hf ESMGb GdcfOis
(3ChdgG (B:s
(3SJQc Gddg dOQc hCYGfc Ydi fjd eSJhYGOJg SCdJ CSYOc Gddg HWGYJg Cf GNJUQ dc bhdkG ai GdfaS (B/(3Y GNJUGQ GdcJGH CQSWh ai GdfaS hdSJ Edi LgOkG ai GSJYeGd GdHdhZ Edi eLGHc s
(3BNQgG (B:s
(3hGNUQfGg ef bhdge Cf GdfaS LhgQ HSjW aJage eG cJHJ Hg Edjc Jcf SYjOkG CSYOc Gddg JYGdi ai OfjGc hCNQJc hGdMeO ddg s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3eUOQ GbJfGA GdCUd (B:s
(3GdeJMa GdHQjWGfi s
Keywords: (3GdadSaI hGdefWbs